A sampling of remarkable groups : Thompson's, self-similar, lamplighter, and Baumslag-Solitar /: Thompson's, self-similar, lamplighter, and Baumslag-Solitar. (2018) - Bonanome, Marianna C; Dean, Margaret H; Putnam Dean, Judith
No abstract available